Metal Ion Sensing, Coordination Chemistry of Some N-,O-Donor Ligands and Synthesis of Substituted Benzenes and Cyclohexanols - Kumar, Sandeep (My University, 2025)
This Thesis contains six chapters. Chapter 1 is about Introduction, Materials and Methods. In this chapter, introduction about fluorescence and various sensing mechanisms are discussed briefly. Some recent literature reports on detection of Zn2+, Cu2+ and Pd2+ ions using different fluorescent probes have been discussed. Recent reports on benzannulation reactions for the synthesis of substituted benzenes have also been described. In Chapter 2, a probe 3,3'-((-(5-(tert-butyl)-2-hydroxy-1,3-phenylene)bis(methaneylylidene))bis(hydrazin-1-yl-2-ylidene))bis(quinoxalin-2(1H)-one) (LH) showed very weak fluorescence (λem = 597 nm) in EtOH/HEPES buffer system (5 mM, pH = 7.4, 8:2, v/v) upon excitation with 419 nm light. Upon adding Zn2+ ion to the probe solution, a huge enhancement in fluorescence (λem = 537 nm) was observed. Jobs plot and single crystal XRD method suggested a 2:1 binding ratio between Zn2+ and LH. A very low detection limit of 95 nM was calculated using LH for detection of Zn2+ ion. In Chapter 3, a heterocyclic probe 1-(imidazo[5,1-a]isoquinolin-3-yl)naphthalen-2-ol (L2H) has exhibited very high fluorescence in MeOH/HEPES buffer system (5 mM, pH = 7.4, 2:8, v/v) at λem = 437 nm when excited with λex = 336 nm. But after addition of Cu2+ and Pd2+ ions the fluorescence got quenched. Jobs plot and mass spectral analysis suggested a 1:2 binding ratio between M2+ (M = Cu, Pd) and L2H. DFT/TDDFT calculation supported the experimentally observed red shifts in absorption spectra due to addition of Cu2+ and Pd2+ ion to probe solution. In Chapter 4, a polypyridine ligand (L3) containing two terpyridine arms was synthesized and utilized in synthesis of two new metal complexes of Co(II) and Mn(II) with compositions [M2(L3)Cl4]2H2O. Molecular structures of these three were established using single crystal XRD method. Taking inspiration from synthesis of terpyridine, Chapter 5 deals with synthesis of 1,2,4,6-tetrasubstituted benzenes from the reaction of aryl methyl ketones and aromatic aldehydes in 3:1 ratio in the presence of 3 equivalents of NaH in one pot condition. The reaction was regioselective in nature. In Chapter 6, changing the ratio of aryl methyl ketone and aromatic aldehyde from 3:1 to 3:2 in the presence of catalytic amount of NaH yielded 1,2,3,4,5-pentasubstituted cyclohexanol. Using this methodology some new and reported substituted cyclohexanols were synthesized.
Manivannan, V.